"Educational Environment"- reflection of MBBS students; in a rural medical college of West Bengal - Hironmoy Roy; Kuntala Ray (Al Ameen Medical College, 2019)
Background: A good learning environment is always essential for quality training and in parallel to enrich the learning environment by identifying its weakness if different arenas. In the state of West Bengal, amongst the existing Government medical colleges, this study is done in a rural medical college, situated in rural area in foothill of Himalaya. Aim and Objectives: To analyze the existing Educational Environment in the North Bengal Medical College, from students' feedback; using the DREEM inventory; and subsequently to frame the recommendations for its betterment (if needed). Methodology: After getting the proper permission from the regulatory bodies and sensitization to the students, the classes of all Phase of MBBS were approached. 142 responses came from Phase 1 MBBS, 133 responses came from Phase 2 MBBS, 97 responses came from Phase 3 Part 1, and 100 responses got collected from Phase 3 part 2 students. All the responses got tabulated in Microsoft excel sheet and against each component of the questionnaire the average got calculated. Result: The mean DREEM score of the institution found to be 123.8/200 i.e. 'more positive than negative'. The 'perception of Learning' gradually declines in higher phases of MBBS. The 'perception of Teachers' is almost equivocal; highest among the Phase2 MBBS class. Least 'academic self perception' has been observed among the Phase 1 MBBS class. Whereas in Phase 3 students the 'atmosphere' perceived to be lower. Socially none is much effluent and for every class it was noted to be low. In total the Phase 1 students quantified the educational environment as 134.2/200, Phase 2 students have quantified as 127.4/200, so for Phase 3(part 1) class as 114.7/200 and the final year class has opined for 118.7/200 (all in the range of "more positive than negative") Conclusions: The present study reveals that all the students on an average perceives their Educational Environment "more positive than negative". However a few lacunae came out of their perception, as- long term learning is not emphasized, lack of support system in "stress", not so-good ward atmosphere, teachers not address empathy- these all are having an impact on revision of the students' learning-assessment plans & programmes.